2016
DOI: 10.1111/cch.12319
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited attachment behaviour and disinhibited social engagement behaviour as relevant concepts in referred home reared children

Abstract: Even without evident links to maltreatment, results of this study suggest clinical significance of inhibited attachment behaviour and disinhibited social engagement behaviour in young home reared children referred for treatment of emotional and behavioural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 30 publications
1
11
0
11
Order By: Relevance
“…These disruptive emotional interactions between a primary caregiver and child, which could influence the behavior of the child, are not always captured within the concept of child maltreatment/neglect. As we reported earlier, more DSEB was associated with more parenting stress in treatment referred home‐reared and foster care children (Scheper et al., ). It might well be possible that higher parenting stress concurs with disruptive emotional interactions between parent and child that could underlie DSEB in home‐reared children.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These disruptive emotional interactions between a primary caregiver and child, which could influence the behavior of the child, are not always captured within the concept of child maltreatment/neglect. As we reported earlier, more DSEB was associated with more parenting stress in treatment referred home‐reared and foster care children (Scheper et al., ). It might well be possible that higher parenting stress concurs with disruptive emotional interactions between parent and child that could underlie DSEB in home‐reared children.…”
Section: Discussionsupporting
confidence: 75%
“…The study was approved by the VU University Medical Center Medical Ethical Review Board (protocol 2013.358). A subsample of the children in this study was also reported on for a cross‐sectional study on disordered attachment behavior in referred home‐reared children (Scheper et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations